2011
DOI: 10.1029/2010je003749
|View full text |Cite
|
Sign up to set email alerts
|

Field reconnaissance geologic mapping of the Columbia Hills, Mars, based on Mars Exploration Rover Spirit and MRO HiRISE observations

Abstract: [1] Chemical, mineralogic, and lithologic ground truth was acquired for the first time on Mars in terrain units mapped using orbital Mars Reconnaissance Orbiter's High Resolution Imaging Science Experiment (MRO HiRISE) image data. Examination of several dozen outcrops shows that Mars is geologically complex at meter length scales, the record of its geologic history is well exposed, stratigraphic units may be identified and correlated across significant areas on the ground, and outcrops and geologic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 72 publications
2
39
0
Order By: Relevance
“…Rock and outcrop targets encountered by Spirit were classified according to their geochemical, spectral, and physical properties [ Ming et al ., ; Morris et al ., ; Squyres et al ., ; McCoy et al ., ; Crumpler et al ., ]. The largest division in inferred strength between rock types is between Adirondack‐class rocks (including Adirondack, Mazatzal, and Humphrey) and rock and outcrop materials found in the Columbia Hills, a distinction noted previously [e.g., Squyres et al ., ].…”
Section: Discussion and Application To Mer Spirit Resultsmentioning
confidence: 99%
“…Rock and outcrop targets encountered by Spirit were classified according to their geochemical, spectral, and physical properties [ Ming et al ., ; Morris et al ., ; Squyres et al ., ; McCoy et al ., ; Crumpler et al ., ]. The largest division in inferred strength between rock types is between Adirondack‐class rocks (including Adirondack, Mazatzal, and Humphrey) and rock and outcrop materials found in the Columbia Hills, a distinction noted previously [e.g., Squyres et al ., ].…”
Section: Discussion and Application To Mer Spirit Resultsmentioning
confidence: 99%
“…Orbital observations had earlier shown that the rim of Gusev was breached by an outflow channel, but Spirit observations indicated that any fluvial sediments within the crater have been buried by basaltic lavas and soil. Spirit's traverse into the Columbia Hills (Crumpler et al, 2011;Squyres et al, 2006a) and Inner Valley (Squyres et al, 2007) found aqueously altered rocks of uncertain origin, soils, and pyroclastic deposits. Spirit's traverse into the Columbia Hills (Crumpler et al, 2011;Squyres et al, 2006a) and Inner Valley (Squyres et al, 2007) found aqueously altered rocks of uncertain origin, soils, and pyroclastic deposits.…”
Section: Geologic Context For Geochemical Data Setsmentioning
confidence: 99%
“…We discuss sedimentation last, but sedimentation presumably began shortly after the formation of the impact crater (Cabrol ; Crumpler et al. ). Spirit found neither the nature nor ubiquity of sediments that were expected from the fact that Gusev crater is the catchment area for Ma'am Vallis (Kuzmin et al.…”
Section: Implications For the Formation Of Alteration Phases In Gusevmentioning
confidence: 99%